Duplicidad gástrica. - Puente Fonseca, Claudio; Corona Mancebo, Sixto; Endi Felfli, Félix; Valdenebro García, Mirtha; Ronda León, Mercedes; Araluce Bertot, Jacobo (Revista Cubana de Pediatría, 2023)
Breve revisión de la literatura médica sobre duplicidad gástrica. Presentación de un caso.